Optimization of a modified QuEChERS method by means of experimental design for multiresidue determination of pesticides in milk and dairy products by GC-MS - Manav, Ozun Gorel; Dinc-Zor, Sule; Alpdogan, Guzin (ELSEVIER SCIENCE BV, 2019)
The aim of this study is to determine optimum extraction and clean up conditions for different pesticide residues in milk and dairy products by using GC-MS. A Box-Behnken design with 3-level 4-variable followed by Plackett-Burman screening design was employed in order to optimize significant variables of the modified QuEChERS method. After the determination of optimal experimental conditions, the proposed method was validated according to SANCO guideline. The method presented recoveries between 72.5% and 120.0% for 25 pesticides, which is satisfactory when one considers the performance criteria detailed in this guideline. The repeatability and within-laboratory reproducibility ranged from 0.95 to 14.62% and from 1.45 to 17.94%, respectively. Also, the method allowed the determination at low detection limits within short analysis time (< 17.5 min). Consequently, application of the developed method to milk and dairy products samples revealed that this method is suitable for routine multi-residue pesticides analysis in terms of high accuracy, precision and efficient.
Keywords: Multi-residue pesticides determination; QuEChERS; Experimental design; GC-MS; Milk; Dairy products; TANDEM MASS-SPECTROMETRY; SOLID-PHASE EXTRACTION; FLAME PHOTOMETRIC DETECTION; LIQUID-LIQUID MICROEXTRACTION; CENTRAL COMPOSITE DESIGN; GAS-CHROMATOGRAPHY; ORGANOPHOSPHORUS PESTICIDES; ALTERNATIVE SORBENTS; SAMPLE PREPARATION; RESIDUE ANALYSIS; Chemistry